Applying Meaningful Learning (NGL and Game) to Improve Students' Scientific Concept Understanding and Scientific Literacy in Reproductive System Material - Andri Rudi Yanto; Yuni Pantiwati; Avina Ridatul Saputri; Tiara Suci Andani; Tasya Novian Indah Sari (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Scientific concept understanding and scientific literacy are essential for students to have. Excellent scientific concept understanding and scientific literacy make it easier for students to learn new material and solve problems they face. This study aims to increase junior high school students' scientific concept understanding and scientific literacy in reproductive system materials by applying meaningful learning with NGL games. The design used in this research is Classroom Action Research (CAR) by Kammi and McTaggart (1988). The research was conducted at SMP Islam Bani Hasyim, Malang Regency, in September 2022 with 20 grade-nine students for the 2022/2023 academic year. Data collection techniques in this study are observation and tests. Data analysis techniques in research are descriptive quantitative and descriptive qualitative The CAR research was carried out in two cycles with the stages of planning, implementing, observing, and reflecting. Applying meaningful learning with the NGL game can improve students' scientific concept understanding and literacy in reproductive system materials.